Pengaruh Transfer antar Pemerintah pada Kinerja Fiskal Pemerintah Daerah Kota dan Kabupaten di Indonesia - Haryo Kuncoro (Economic Journal of Emerging Markets, 2004)
The main problem of this research was to analyze the local government response to the intergovernmental transfers. The main objective of this research was to get a deeper analytical results about the contribution of the intergovernmental transfers on the local own revenue, routine and development expenditures in the case of district and municipality gov¬ernments in Indonesia over the period of 1988-2002.Using the simultaneous equation system, we concluded that the intergovernmental transfers stimulate the increase of the local government expenditures larger than that of the local own revenue. It seems that the dependency of local government onto the intergovern¬mental transfers will be worse. The local governments in the long run tend to use the exter¬nal borrowing to finance the increase of their expenditures. Those results above suggest that (1) the distribution of intergovernmental transfers among regions should consider the local tax effort, and (2) services minimum standard plays an important role to realize the expen¬ditures efficiency.Keywords: Intergovernmental transfer, fiscal performance, simultaneous equation.